Pulmonary Arteriovenous Malformation (AVM) Causing Tension Hemothorax in a Pregnant Woman Requiring Emergent Cesarean Delivery - Nidhi Sood; Nikhil Sood; Vibhu Dhawan (Pulmonary Medicine)
Pulmonary arteriovenous malformations (PAVMs), although most commonly congenital, are usually detected later in life. We present a case of a 25-year-old woman with no previous history of AVM or telangiectasia, who presented with life-threatening hypoxia, hypotension, and pleuritic chest pain in 36th week of gestation. Chest tube placement revealed 4 liters of blood. Patient was subsequently found to have bleeding pulmonary AVM as the source of hemothorax. Successful embolisation of the bleeding vessel followed by thoracoscopic evacuation of the organized clot relieved the hypoxia. Further screening for AVM revealed large splenic AVM for which patient underwent splenectomy in the coming months.